2022
DOI: 10.1021/acsomega.2c01400
|View full text |Cite
|
Sign up to set email alerts
|

Green Route Synthesis and Characterization Techniques of Silver Nanoparticles and Their Biological Adeptness

Abstract: The development of the most reliable and green techniques for nanoparticle synthesis is an emerging step in the area of green nanotechnology. Many conventional approaches used for nanoparticle (NP) synthesis are expensive, deadly, and nonenvironmental. In this new era of nanotechnology, to overcome such concerns, natural sources which work as capping and reducing agents, including bacteria, fungi, biopolymers, and plants, are suitable candidates for synthesizing AgNPs. The surface morphology and applications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 161 publications
2
40
1
Order By: Relevance
“…Hence, it can be deduced that this absorption peak should be the surface plasmon resonance absorption peak of Ag nanoparticles in Ag (0.33)-PVA/MXene (2)-PDDA. 48 Here, the plasmon resonance absorption wavelength is not close to the laser excitation wavelength. However, the results reported previously indicate that Ag nanoparticles can exhibit a strong SERS effect for the adsorbed organic molecules, although the laser excitation wavelength (632.8 nm) is not close to their plasmon wavelength (423 nm).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Hence, it can be deduced that this absorption peak should be the surface plasmon resonance absorption peak of Ag nanoparticles in Ag (0.33)-PVA/MXene (2)-PDDA. 48 Here, the plasmon resonance absorption wavelength is not close to the laser excitation wavelength. However, the results reported previously indicate that Ag nanoparticles can exhibit a strong SERS effect for the adsorbed organic molecules, although the laser excitation wavelength (632.8 nm) is not close to their plasmon wavelength (423 nm).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Based on the XRD spectrum of the AE-AgNP, the average AgNP size was 39.78 nm. A few unassigned peaks were detected, which may have been caused by the existence of bioorganic compounds or proteins in the extracts that crystallized on the surface of the AgNP (Sharma et al, 2022). In a similar observation, the AgNPs synthesized from the flower extract of Mangifera indica also showed a similar pattern of peaks in XRD analysis (Ameen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The sharp peak at 1315.45 cm −1 indicated C(O)-O stretching vibrations; the peak at 1031.91 cm −1 indicated the involvement of reducing sugars 52 . Furthermore, Al Masoud et al demonstrated the use of FTIR to detect biomolecules for reducing Ag+ ions and capping ginger extractproduced AgNPs 53 . The ndings showed that the signi cant peaks at 1057, 1386, 1620, and 3417 cm− 1 corresponded to primary alcohols and NO 3 and C−N stretching vibrations of aliphatic and aromatic amines, respectively 54 .…”
Section: Discussionmentioning
confidence: 99%